(untitled) (Nepal Journal of Environmental Science, 2016)
Road vegetation is an effective way to mitigate road generated particulates. Green belts with high Air Pollution Tolerance Index (APTI) value in the urban centers play an important role in the amelioration of the air quality. The APTI of the trees with higher abundance were examined for bio-chemical parameters such as pH, ascorbic acid, total chlorophyll and relative water content. The APTI value of tree species varied from 5.56 (Punica granatum) to 79.99 (Populous deltoids). Higher the APTI value, higher is the tolerance towards air pollution. Among the tree species, Jacaranda mimosifolia, Pinus roxburghi, Ficus benjamin, Celtis australis, Alnus nepalensis, Callistemon lanceolatus, Schima wallichi, Pyrus pyrifolia and Punica granatum were found sensitive, whereas Prunus persia, Populus deltoides, Thuja sp. and Grevillea robusta were found to be the most tolerant species. The green belts constituting higher number of tolerant to moderately tolerant species of trees results in better air pollution sink and air quality refinement. In order to find plants with good APTI, further extensive studies should be carried out and valley plantation program should give priority of those plants having higher APTI value.